Characterizations of Ordered Semigroups by New Type of Interval Valued Fuzzy Quasi-Ideals. (25th May 2014) - Tang, Jian; Xie, Xiangyun; Luo, Yanfeng
Abstract : The concept of non-k -quasi-coincidence of an interval valued ordered fuzzy point with an interval valued fuzzy set is considered. In fact, this concept is a generalized concept of the non-k -quasi-coincidence of a fuzzy point with a fuzzy set. By using this new concept, we introduce the notion of interval valued ( ∈ ¯, ∈ ¯ ∨ q k ¯ ) -fuzzy quasi-ideals of ordered semigroups and study their related properties. In addition, we also introduce the concepts of prime and completely semiprime interval valued ( ∈ ¯, ∈ ¯ ∨ q k ¯ ) -fuzzy quasi-ideals of ordered semigroups and characterize bi-regular ordered semigroups in terms of completely semiprime interval valued ( ∈ ¯, ∈ ¯ ∨ q k ¯ ) -fuzzy quasi-ideals. Furthermore, some new characterizations of regular and intra-regular ordered semigroups by the properties of interval valued ( ∈ ¯, ∈ ¯ ∨ q k ¯ ) -fuzzy quasi-ideals are given.